2014
DOI: 10.1038/nature13668
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of regulatory information and circuits across distant species

Abstract: SummaryDespite the large evolutionary distances, metazoan species show remarkable commonalities, which has helped establish fly and worm as model organisms for human biology1,2. Although studies of individual elements and factors have explored similarities in gene regulation, a large-scale comparative analysis of basic principles of transcriptional regulatory features is lacking. We mapped the genome-wide binding locations of 165 human, 93 worm, and 52 fly transcription-regulatory factors (RFs) generating a to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
184
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 200 publications
(200 citation statements)
references
References 53 publications
15
184
1
Order By: Relevance
“…These neurons tended to contain TSS regions and may represent high-occupancy target (HOT) regions, genomic loci bound by multiple TFs that often mark the promoters of highly expressed genes (Moorman et al 2006;Gerstein et al 2010;Negre et al 2011;Yip et al 2012). We found that HOT regions, as determined by Boyle and colleagues were significantly enriched in long-range interactions (P = 5.9 3 10 À62 , Fisher's exact test) and that HOT regions had a strong preference to interact with other HOT regions (P = 4.5 3 10 À271 , Fisher's exact test) (Boyle et al 2014). Taken together these findings support the model that DNA looping brings active promoters into distinct nuclear subcompartments termed ''transcription factories.…”
Section: Genome-wide Map Of Regulatory Interactionsmentioning
confidence: 73%
“…These neurons tended to contain TSS regions and may represent high-occupancy target (HOT) regions, genomic loci bound by multiple TFs that often mark the promoters of highly expressed genes (Moorman et al 2006;Gerstein et al 2010;Negre et al 2011;Yip et al 2012). We found that HOT regions, as determined by Boyle and colleagues were significantly enriched in long-range interactions (P = 5.9 3 10 À62 , Fisher's exact test) and that HOT regions had a strong preference to interact with other HOT regions (P = 4.5 3 10 À271 , Fisher's exact test) (Boyle et al 2014). Taken together these findings support the model that DNA looping brings active promoters into distinct nuclear subcompartments termed ''transcription factories.…”
Section: Genome-wide Map Of Regulatory Interactionsmentioning
confidence: 73%
“…No appreciable pattern of sequence similarity or changes or existence and numbers of the regulatory motifs abscisic acid response element, gibberellin-responsive element response element, low-temperature responsive element, skinhead-1 binding element, and/or antioxidant-response element were found in the 500, 1,000, and 2,000 bp upstream of the coding sequences of SL2 and T8 oleosin genes. Our noncommittal finding reflects the current insufficient knowledge of the mechanism of changes in regulatory motifs in gene promoters leading to the evolutionary alteration of cell/tissue expression in multicellular organisms (Boyle et al, 2014).…”
Section: T Oleosins Evolved From Sl Oleosin and Present In Tapeta Ofmentioning
confidence: 94%
“…To further investigate the relationship (Locke et al 2013) and computational nucleosome occupancy model scores (Kaplan et al 2009) Nucleosome fragility in C. elegans between TF binding and fragility, we broke TFBSs into groups depending on the number of TFs bound at a site. Although the majority of TFBSs identified in C. elegans are bound by a single factor, some sites are bound by many TFs Boyle et al 2014;Chen et al 2014). Fragility scores increased with the number of TFs bound at a single TFBS (Fig.…”
Section: Trans-factors Increase Nucleosome Fragilitymentioning
confidence: 99%